(untitled) (Prilozi za književnost, jezik, istoriju i folklor, 2023)
Dimitrije Davidović’s printing house did not fulfill the expectations of Serbs, nor his personal ones, during its three years of work in Vienna. Because he did not get the general printing right, he got into big financial trouble. Using his acquaintance with the rich Greek-Aromanian family Darvar, he tried to overcome these problems by printing books in Greek. Taking into account the fact that this is still unknown in Serbian science, we present the available data on it, considering it important for the Serbian national bibliography, and in this way specific international cultural relations are additionally presented. At the end of the paper, a list of all Greek books that Davidović printed is given.